Dealing with complex and ill-structured problems: results of a Plan-Do-Check-Act experiment in a business engineering semester. (4th July 2017) - Riis, Jens Ove; Achenbach, Marlies; Israelsen, Poul; Kyvsgaard Hansen, Poul; Johansen, John; Deuse, Jochen
ABSTRACT: Challenged by increased globalisation and fast technological development, we carried out an experiment in the third semester of a global business engineering programme aimed at identifying conditions for training student in dealing with complex and ill-structured problems of forming a new business. As this includes a fuzzy front end, learning cannot be measured in traditional, quantitative terms; therefore, we have explored the use of reflection to convert tacit knowledge to explicit knowledge. The experiment adopted a Plan-Do-Check-Act approach and concluded with developing a plan for new learning initiatives in the subsequent year's semester. The findings conclude that (1) problem-based learning develops more competencies than ordinarily measured at the examination, especially, the social/communication and personal competencies are developed; (2) students are capable of dealing with a complex and ambiguous problem, if properly guided. Four conditions were identified; (3) most students are not conscious of their learning, but are able to reflect if properly encouraged; and (4) improving engineering education should be considered as an organisational learning process.